Workplace ergonomic assessment pada komunitas pekerja internet marketing society - Fauzi, Ekha Rifki; Palino, Riski Rizal (Institut Teknologi Dirgantara Adisutjipto, 2022)
Regular use of computers in the workspace contributes to suffering from many risk factors associated with musculoskeletal disorders (MSDs). Ergonomic principles is a determining factor of comfort and increased worker productivity at work. Ergonomics is also very important for workers who use computers. Working with computers is at high risk of suffering from a variety of complaints, including having the three biggest risk factors: back posture, repetition, and static strength. Preventive measures can minimize the negative impact of the main risks above. The purpose of this study is to assess and measure the ergonomics of the Internet Marketing Society's workplace workers. This service research uses observational methods from survey results with questionnaires distributed via google form. The total sampling is 33 workers from the Internet Marketing Society. The results show that 54.5% of workers do not know about ergonomics, 75.8% of workers do not use wrist and arm support devices. In the complaint problem, most of the workers experienced muscle pain 27.3% and back pain 24.2%, and 24.2% workers experienced shoulder conditions that were not relaxed while working. Based on these results, it is concluded that workers need to implement the principles of K3 and ergonomics in their work while working with computers.